The prevalence and clinical consequences of TORCH infection in biliary atresia and non-biliary atresia cholestatic disorders - Marwa A Gouda1, Yara Elsaadawy2, Marwa Sabry Rizk3*, Waheed Hussein Elsaidy4, Ahmed Yousef4, Kawthar Ibraheem Mohamed2, Amira Saied M Abdelhady2, Ahmed A Ghandour5, Noha F. Zahran6; Mona M. El-Derbawy6 (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Infection with Toxoplasma, Rubella, Cytomegalovirus (CMV), and Herpes simplex virus (HSV) types 1 and 2 have been accused over the past years as causative factors for neonatal cholestasis, including biliary atresia (BA). This assemblage of organisms could generate severe manifestations, especially in immunocompromised hosts, which have the potential to be prevented and treated. Objective: The current research aimed at identifying the immunity to TORCH infection in biliary atresia and non-biliary atresia cholestatic disorders and identifying the most accompanied complications. Subjects and Methods: This cross-sectional, analytical comparative study involved the enrollment of 100 pediatric patients using systemic random sampling methodology; 50 infants were diagnosed as having BA, and others suffered from other cholestatic from National Liver Institute (NLI) attendees. These individuals were examined for TORCH immunity using imaging, serological biomarkers, and molecular diagnosis of CMV infection. Results: The two groups showed similar TORCH infection rates (P>0.05). Among the patients, 24% tested positive for CMV IgM, 23.3% tested positive for CMV by polymerase chain reaction (PCR), 16% tested positive for Rubella, 41% tested positive for Toxoplasma, 28% tested positive for HSV 1 and 19% tested positive for HSV 2 IgM. The most frequently observed complications were developmental delay (32%), microcephaly (11%), ocular issues (11%), low birth weight (9%), congenital heart diseases (6%), and hydrocephalus (4%). However, there was no statistically significant disparity between the two groups’ distribution of these reported complications. Female infants and a history of positive consanguinity were higher in the BA cholestatic infants. Conclusion: Immunity to toxoplasmosis was the highest in the present study, followed by CMV, HSV, and Rubella. Among the accompanied complications, developmental delay followed by microcephaly was the most presented. Therefore, screening for TORCH complex in diagnosed with cholestasis should be routinely performed.